2016
DOI: 10.1063/1.4955137
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of graphene and graphene nanostructures by ion implantation and pulsed laser annealing

Abstract: In this paper, we report a systematic study that shows how the numerous processing parameters associated with ion implantation (II) and pulsed laser annealing (PLA) can be manipulated to control the quantity and quality of graphene (G), few-layer graphene (FLG), and other carbon nanostructures selectively synthesized in crystalline SiC (c-SiC). Controlled implantations of Si À plus C À and Au þ ions in c-SiC showed that both the thickness of the amorphous layer formed by ion damage and the doping effect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Thermal behavior of carbon in LiNbO 3 is studied by post-implantation annealing. By referring to the diffusion of implanted C in Ni and Cu, which usually requires a temperature around 900°C [18][19][20][21][22][23][24][25], the highest temperature in the present experiment is set at 900°C. However, considering that the different LiNbO 3 samples have different tolerance to high temperature environment, thin-film LiNbO 3 crystal and bulk LiNbO 3 crystal were annealed under different temperatures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal behavior of carbon in LiNbO 3 is studied by post-implantation annealing. By referring to the diffusion of implanted C in Ni and Cu, which usually requires a temperature around 900°C [18][19][20][21][22][23][24][25], the highest temperature in the present experiment is set at 900°C. However, considering that the different LiNbO 3 samples have different tolerance to high temperature environment, thin-film LiNbO 3 crystal and bulk LiNbO 3 crystal were annealed under different temperatures.…”
Section: Methodsmentioning
confidence: 99%
“…At present, the transition metal nickel (Ni) or copper (Cu) is usually used as catalyst for the formation of graphene by carbon implantation. Researchers usually implant the carbon that its dose is equivalent to the carbon content of one to four layers of graphene into nickel or copper film, after annealing, the carbon precipitates from nickel or copper film to form graphene [18][19][20][21][22][23][24][25]. However, in the method of forming graphene by ion implantation, removing the intermediate process of transition metal as a catalyst will be more attractive.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to control the number of layers of synthetic graphene may be possible by precisely adjusting the implantation dose (Garaj et al, 2010;Zhang et al, 2013). At present, transition metal nickel or copper are usually used to form graphene by carbon implantation (Garaj et al, 2010;Baraton et al, 2011a;Mun et al, 2012;Wang et al, 2013;Zhang et al, 2013;Lee et al, 2014;Kim et al, 2015;Wang et al, 2016). As the solubility of carbon in nickel decreases significantly with the decline of temperature, the carbon dissolved in nickel at high temperature will become saturated with the decrease of annealing temperature, and with the progress of thermal diffusion, they will eventually spread to the surface of the metal to form a single-layer or multi-layer graphene (Lander et al, 1952;Berry, 1973;Baraton et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…5.9(a). It has been suggested that the sputtering of Si from SiC, forming carbon rich clusters, is responsible for this density loss and in fact this has been used to lower the growth temperature of graphene/graphite on SiC [95,96]. As shown in Fig.…”
Section: -Neutron and X-ray Reflectivitymentioning
confidence: 99%